Association of serum lipids with inflammatory bowel disease: a systematic review and meta-analysis - Chen, Hongxin; Li, Weiyang; Hu, Jingyi; Xu, Feng; Lu, Yizhou; Zhu, Lei; Shen, Hong (Frontiers in Medicine, 2023)
Background: Serum lipid levels seem to be abnormal in Inflammatory bowel disease (IBD). However, the specific manifestation of abnormal serum lipid levels in IBD are heterogeneous among studies and have not been sufficiently determined yet. Methods: PubMed, EMBASE, and Cochrane Library databases were searched. Serum lipid levels were compared between IBD patients and Health individuals, Crohn’s (CD) and ulcerative colitis (UC), active and inactive, mild and non-mild patients, respectively. Meta-analyses were performed by using a random-effect model. Weight mean difference (WMD) with 95% confidence intervals (CIs) were calculated. Results: Overall, 53 studies were included. Compared with healthy controls, IBD patients had significantly lower TC (WMD = -0.506, 95%CI = -0.674 to -0.338, P < 0.001), HDL-c (WMD = -0.122, 95%CI = -0.205 to -0.039, P=0.004), and LDL-c (WMD = -0.371, 95%CI = -0.547 to -0.194, P < 0.001) levels. CD groups had a significantly lower TC (WMD = -0.349, 95%CI = -0.528 to -0.170, P < 0.0001) level as compared to UC groups. Active IBD and non-mild UC groups had significantly lower TC (WMD =-0.454, 95%CI = -0.722 to -0.187, P = 0.001) (WMD =0.462, 95%CI = 0.176 to 0.748, P = 0.002) and LDL-c (WMD =-0.225, 95%CI = -0.445 to -0.005, P = 0.045) (WMD =0.346, 95%CI = 0.084 to 0.609, P = 0.010) levels as compared to inactive IBD and mild UC groups, respectively. Conclusions: The overall level of serum lipids in IBD patients is lower than that of healthy individuals and is negatively associated with disease severity.